A Model of Factors Affecting the Use of Personal Protective Equipment Using a Path Analysis among PLTU Contractor Workers in East Java - Wisdha Riezqi Ginandhani; Dewi Kurniasih; Farizi Rachman (Universitas Airlangga, 2021)
Introduction: Based on the survey data in one of the PLTUs in East Java from January-November 2019, there were 9.134 findings of non-compliance with PPE. In addition, based on the audit data from October to November 2019, there were 125 findings of non-compliance with the use of PPE. The factors causing this non-compliance could be seen from the characteristics of the workers or could be based on the Health Belief Model (HBM) approach through 6 constructs. Based on these data, this article aimsto analyze a model of factors that have a direct and indirect effect on the use of PPE on PLTU contractor workers in East Java. The researchers used the Health Belief Model approach because the use of PPE for workers is an effort related to healthy behavior in the workplace. Methods: This research was a quantitative research. The total sample was 100 workers from a population of 400 contractors workers, based on the Slovin methodand as a fulfillment of the path analysis requirement. The analyses of direct and indirect effects between variables used a path analysis method. Results: The results of data processing showa direct effect of perceived benefits (t=4,837), cues to action (t=5,990), perceived severity (t=2,131), knowledge (t=3,183), and perceived susceptibility (t=2,212) on the use of PPE, while education iis known to have an indirect effect on the use of PPE through knowledge (t=2,222). Conclusion: Perceived benefits, cues to action, perceived severity, knowledge, and perceived susceptibility have a direct effect on the use of PPE. However, education has an indirect effect on the use of PPE through knowledge.Keywords: health belief model, occupational diseases, path analysis, personal protective equipment